Food Fish, Commercial Fish, and Fish to Support a Moderate Livelihood: Characterizing Aboriginal and Treaty Rights to Canadian Fisheries - C. Harris, Douglas; Millerd, Peter (Arctic Review on Law and Politics, 2010)
The Aboriginal peoples of Canada stand in a different legal relationship to the fisheries than non-Aboriginal Canadians. They do so by virtue of a long history with the fisheries that precedes non-Aboriginal settlement in North America, and because of the constitutional entrenchment of Aboriginal and treaty rights in Canadian law. This article describes the characterizations of Aboriginal and treaty rights to fish in Canadian law and discusses what it means for rights characterized in terms of food fishing, commercial fishing, and fishing to support a moderate livelihood, to receive constitutional protection. The article then problematizes these characterizations and suggests that the simplest and broadest characterization, that is, of a right to fish without restriction as to purpose or use of fish, best coincides with the goals of effective management and fair distribution.Keywords: Fisheries, Indigenous people, Aboriginal and treaty rights, Canada.Citation: Arctic Review on Law and Politics, vol. 1, 1/2010 p. 82–107. ISSN 1891-6252